2019
DOI: 10.1002/mnfr.201900248
|View full text |Cite
|
Sign up to set email alerts
|

Daily Supplementation with Fresh Angelica keiskei Juice Alleviates High‐Fat Diet‐Induced Obesity in Mice by Modulating Gut Microbiota Composition

Abstract: Scope: Angelica keiskei is associated with several health benefits, but little is known about the effect of A. keiskei juice (AKJ), which is rich in polyphenols, coumarins, and other healthful agents, on high-fat diet-induced obesity or its relationship with intestinal microbiota composition changes. Methods and results: C57BL/6 mice are fed either a normal diet (ND group; n = 8), a high-fat diet (HFD group; n = 8), or a high-fat diet supplemented with AKJ (AKJ group; n = 8) for 10 weeks. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 46 publications
(72 reference statements)
4
31
0
Order By: Relevance
“…We found that even if they eat the same high calorie fat-rich foods, seabuckthorn intake could not only reduce food intake to prevent the development of obesity, but also reduce the utilization efficiency of food and energy. Similar results were obtained in the dietary intervention of Phaseolus vulgaris extract, fresh angelica keiskei juice, and mulberry ethanol extract on obesity induced by a high-fat diet [12,21,22].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We found that even if they eat the same high calorie fat-rich foods, seabuckthorn intake could not only reduce food intake to prevent the development of obesity, but also reduce the utilization efficiency of food and energy. Similar results were obtained in the dietary intervention of Phaseolus vulgaris extract, fresh angelica keiskei juice, and mulberry ethanol extract on obesity induced by a high-fat diet [12,21,22].…”
Section: Discussionsupporting
confidence: 82%
“…Obesity is defined as the accumulation of excess adipose tissue, accompanying the increase of body weight and fat deposition in the liver, causing corresponding metabolism dysfunction. Accumulating evidence showed that the daily consumption of foods rich in bioactive compounds, such as fruits and vegetables, could confer a beneficial effect on anti-obesity and obesity-association metabolism diseases [21]. In our study, the results showed that daily supplementation with seabuckthorn freeze-dried powder at 4.0 mg/(g.d. body weight) could significantly decrease body weight, Lee's index, adipose tissue weight, liver weight, and other obesity-related indexes.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations